Understanding the decision-making process in homeowner energy retrofits - Shima Ebrahimigharehbaghi (A+BE: Architecture and the Built Environment)
In 2020, owner-occupied housing accounted for 57% of the housing stock in the Netherlands. Homeowners are fully responsible for the implementation of energy retrofits. Moreover, the processes of energy retrofitting are complex and homeowners face problems such as finding financial support, reliable information and contractors. The complexity of implementing energy retrofits may discourage homeowners from continuing the process and achieving the expected benefits. Behavioural aspects and transaction costs (TC) are among the most important factors influencing consumer decision-making processes. Behavioural factors primarily illustrate a range of personal, contextual, and external factors that influence the decision-making process of homeowners. These include cognitive awareness and biases, attitudes and beliefs, experience and skills, homeowner characteristics, sociodemographic characteristics, property characteristics, and the behaviour of others. TC are any hidden costs that influence decision making but are not included in the direct physical costs of renovation services and products. This dissertation developed an integrated framework of behavioural factors and TC that impede the decisionmaking process for energy retrofits. Key findings include (1) the significant importance of behavioural factors and TC barriers. (2) the behavioural factors are particularly important in the early stages of energy retrofits and the TC barriers after the final decision. (3) the importance of behavioural factors and TC barriers differs according to the type of energy retrofit and non-energy retrofit. (4) Accounting for cognitive biases significantly improves the prediction of households' actual decisions about energy retrofits. This modelling is more accurate than the model that assumes households make rational decisions.